2014
DOI: 10.48550/arxiv.1410.3274
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Crossed S-matrices and Character Sheaves on Unipotent Groups

Abstract: Let k be the algebraic closure of a finite field F q of characteristic p. Let G be a connected unipotent group over k equipped with an F q -structure given by a Frobenius map F : G −→ G. We will denote the corresponding algebraic group defined over F q by G 0 . Character sheaves on G are certain special objects in the triangulated braided monoidal category D G (G) of bounded conjugation equivariant Q l -complexes (where l = p is a prime number) on G. Boyarchenko has proved that the "trace of Frobenius" functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(24 citation statements)
references
References 7 publications
(21 reference statements)
0
24
0
Order By: Relevance
“…(ii) The definition of the crossed S-matrix presented here is slightly different from that given in [De1]. Firstly, in op.…”
Section: The Crossed S-matrix Associated With a Modular Autoequivalencementioning
confidence: 98%
See 4 more Smart Citations
“…(ii) The definition of the crossed S-matrix presented here is slightly different from that given in [De1]. Firstly, in op.…”
Section: The Crossed S-matrix Associated With a Modular Autoequivalencementioning
confidence: 98%
“…In [De1] it was shown that the transition matrix between the irreducible characters in the L-packet associated with e and the "trace of Frobenius" functions of F -stable character sheaves CS e (G) F is the crossed S-matrix S(M e , F ). We refer to [BD], [De1], [De2] for a detailed exposition.…”
Section: Motivation From the Theory Of Character Sheavesmentioning
confidence: 99%
See 3 more Smart Citations